2002
DOI: 10.1046/j.1439-0272.2002.00500.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of experimental varicocele in rats on testicular oxidative stress status

Abstract: The present experiments were undertaken to determine the levels of MDA, SOD and catalase in the testis of adolescent rats with experimental left varicoceles. Male Wistar rats, 7 weeks old and weighing 160-170 g, were randomly allocated into three groups. The first group of rats underwent partial ligation of the left renal vein (n = 15). The second group of rats underwent a sham operation (n = 7) and the third group acted as controls (n = 7). Animals were sacrificed 6 weeks after surgery and dilatation of the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 34 publications
1
17
1
Order By: Relevance
“…It was postulated that increasing levels of MDA in testicular biopsies of infertile men are associated with higher grades of varicocele [22]. In another study by the same author, they could not find a relationship between oxidative status and testicular dysfunction in adolescent rats with varicocele [23].…”
Section: Discussionmentioning
confidence: 95%
“…It was postulated that increasing levels of MDA in testicular biopsies of infertile men are associated with higher grades of varicocele [22]. In another study by the same author, they could not find a relationship between oxidative status and testicular dysfunction in adolescent rats with varicocele [23].…”
Section: Discussionmentioning
confidence: 95%
“…However, the exact aetiology of this condition remains unknown. Several studies have suggested that oxidative stress, which is mainly caused by reactive oxygen species (ROS), is involved in the pathogenesis of varicocele in human and rat (Köksal et al, 2000(Köksal et al, , 2002Romeo et al, 2003). Under normal conditions, antioxidants maintain ROS at low levels.…”
Section: Introductionmentioning
confidence: 99%
“…The levels of lipid peroxidation products are increased in testis and semen in patients with varicocele (Sharma and Agarwal, 1996;Köksal et al, 2002). A specific and stable end-product of lipid peroxidation, the aldehyde 4-hydroxy-2-nonenal (4-HNE), can diffuse within, or even escape from, the cell and attack targets far from the site of the original free radical event (Esterbauer et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…As observed in this study, the MDA level significantly elevated in varicocele-induced rat compared to Control group. MDA levels increased in the semen of patients with varicocele (Koksal et al, 2003;Cervellione et al, 2006) so, increased MDA levels is associated with higher grades of varicocele (Koksal et al, 2002).…”
Section: Discussionmentioning
confidence: 98%
“…Surgical varicocele involves partial obstruction of the left renal vein, causing a varicosity of the left spermatic vein (Koksal et al, 2002). However, the mechanisms responsible for impaired spermatogenesis in animals with iatrogenically induced varicoceles remains unclear.…”
Section: Discussionmentioning
confidence: 99%